DEVELOPING ENGLISH READING MATERIALS BASED ON PROBLEM BASED LEARNING FOR VOCATIONAL STUDENTS OF COMPUTER NETWORK ENGINEERING IN SMK CINTA RAKYAT PEMATANG SIANTAR - Benny Saragih; Amrin Saragih (Universitas Negeri Medan, 2021)
DEVELOPING ENGLISH READING MATERIALS BASED ON PROBLEM BASEDLEARNING FOR VOCATIONAL STUDENTS OF COMPUTER NETWORKENGINEERING IN SMK CINTA RAKYAT PEMATANG SIANTAR* Benny Saragih** Prof. Amrin Saragih, M.A., Ph.D.ABSTRACTSaragih, Benny, Registration Number: 2133121015, Developing English Reading MaterialsBased on Problem Based Learning for Vocational Students of Computer NetworkEngineering in SMK Cinta Rakyat Pematang Siantar. A Thesis. English EducationProgram, State University of Medan, 2020.This research was aimed to develop appropriate reading materials based on Problem BasedLearning for the eleventh-grade students of Computer Network Engineering program in SMKCinta Rakyat Pematang Siantar. This study was conducted by using the Research andDevelopment design through five phases, such as; a. gathering information and data, b; analyzingdata, c. designing new materials, d. validating by experts, and e. developing the final product. Thesubject of this study was the eleventh-grade computer network engineering students of SMKCinta Rakyat Pematang Siantar. The data were collected from the existing textbook, syllabus,interview with English teacher and distributing questionnaires for 25 students. Based on the needanalysis, it was concluded that the students were in need of appropriate reading materials whichare related to computer science, particularly in form of procedure texts. In response to thisinformation, some relevant and appropriate reading materials were developed, namely; a. How tostart Windows PowerShell, b. Installing Avast Antivirus, c. How to Create Ad-hoc Connection,and d. Troubleshooting Computer Problems. These developed procedure text have been revisedand validated by a team of experts which consisted of an English lecturer and an English teacherbefore acquiring the final product. The first expert evaluated the final product with a score of 4.12from the total of 5 points. The second expert evaluated the final product with a score of 4.03 fromthe total of 5 points. Based on the Likert scale, the final product is categorized as suitable withstudents‟ need. Therefore, the developed reading materials are considered appropriate for theeleventh-grade students of Computer Network Engineering program in SMK Cinta RakyatPematang Siantar.Keywords: Research and Development, Vocational School, English for Specific Purposes,Computer Network Engineering